A comprehensive study of ALPs from B-decays - Deepanshu Bisht; Sabyasachi Chakraborty; Atanu Samanta (Journal of High Energy Physics)
Abstract We present a comprehensive study of axion-like particles (ALPs) through flavor changing neutral current processes, such as B → Ka followed by a → hadronic, γγ, μ + μ − channels. Our generic framework encompasses different ultraviolet scenarios similar to KSVZ, DFSZ and flavorful axions etc. Starting from the effective Lagrangian written at the high scale, we compute the anomalous dimension matrix, taking into account all one-loop and relevant two-loop contributions. The latter is most important for the KSVZ and heavy QCD axion scenarios. We recognized that such two-loop diagrams can have both ultraviolet (UV) and infrared (IR) divergences. We show explicitly that UV divergences cancel by inserting appropriate counterterms, which are new operators involving the axion field and required to be present at the UV itself, to renormalize the theory. On the other hand, the cancellation of IR divergences is subtle and demonstrated through matching with the effective theory at the electroweak scale. We also utilize chiral perturbation theory and vector meson dominance framework to compute the decay and branching fractions of the ALP pertaining to our framework. We find that for KSVZ-like scenario, axion decay constant, f a ≲ 1 TeV can be ruled out. The bound becomes stronger for the DFSZ and Flaxion-like models, reaching upto 104 TeV and 106 TeV, respectively. We also provide projections on the parameter space based on 3 ab−1 data from Belle II and 300 fb−1 data from LHCb.